Use of urinary biomarkers of ovarian function in domestic Chinchilla lanigera: Assessing protocols for exogenous regulation of the hypothalamic-pituitary-gonadal axis - Verónica I. Cantarelli; Gabriela Mastromonaco; Georgina Galeano; Marta Fiol de Cuneo; Marina F. Ponzio (Theriogenology Wild, 2024)
Due to the high value of its fur, indiscriminate hunting reduced Chinchilla lanigera wild populations virtually to the verge of extinction (IUCN critically endangered, CITES Appendix I). A key aspect for the implementation of ex-situ breeding programs for wild chinchilla depends on the integration of data obtained from assisted reproduction techniques applied to its domestic congener. One of the most widely used techniques is ovulation induction through the injection of exogenous synthetic drugs. In farm animals, ovarian inactivity allows for a more consistent response to inducer injection. Therefore, the objective in this study was to monitor and evaluate the endocrine patterns of ovarian dynamics and in vivo fertilization rates after exogenous ovarian activation in chinchillas using GnRH analogue and eCG. Seven ovulation induction protocols were tested in females (2–5 years of age) and urine samples were collected before, during and one week after inductor injections. Samples were analyzed for creatinine (Sigma #C3613), estrone conjugates and pregnanediol glucuronides (PdG-R13904, EC-R522–2, C.Munro) by EIA. The endocrine patterns of this species are not necessarily associated with behavioral signs of estrus. Therefore, non-invasive hormonal monitoring remains the only method that allows us to accurately explore ovarian activity. A longitudinal profile was obtained for each hormone and female. The results of our first experiment clearly showed that GnRH administration elicited a regular response only after a threshold value of 10 µg, although of little significance. The use of lower doses was not sufficient to achieve ovarian stimulation while higher doses of GnRH apparently resulted in the suppression of follicular activity, probably due to the effects of a negative feedback of GnRH over its release in the hypothalamus. Although both eCG doses produced similar responses, the 50 I.U. (0.1 I.U./g) dose caused a more powerful and steady response. A progressive increase in the concentrations of EC and PdG metabolites was also evidenced. Finally, the results regarding the pregnancy percentages obtained after the use of any of the protocols in farm animals were very limited, reaching maximum values of 17.2% whereas the control animals reached a percentage of 6.2%.